Simulador de crecimiento y producción para Pino híbrido F2 cultivado en el noroeste de Misiones, Argentina = Growth and production simulator for F2 hybrid Pine cultivated in northwestern Misiones, Argentina - Keller, Aldo Esteban; Crechi, Ernesto Hector (Facultad de Ciencias Forestales, Universidad Nacional de Misiones (UNaM) y EEA Montecarlo, INTA, 2024)
The forest growth simulator Plafornea has been used since 2013 as a support tool for forest management. New models allow its use with a new species. The objective of this work is to present the F2 hybrid pine growth simulator. The program allows estimating the future production of plantations in deep red soils in the northwestern zone of the province of Misiones. It shows results of growth, biomass and products, defined by its thin tip diameter and length. Economic indicators can be estimated in order to select the most convenient management. Simulations can be saved for later consultation or modification.